Outcomes of nosocomial viral respiratory infections in high-risk neonates - Zinna, Shairbanu; Lakshmanan, Arthi; Tan, Shin; McClaughry, Rebecca; Clarkson, Martin; Soo, Shiu; Szatkowski, Lisa; Sharkey, Don (American Academy of Pediatrics, 2016)
BACKGROUND AND OBJECTIVE: Neonatal respiratory disease, particularly bronchopulmonary dysplasia, remains one of the leading causes of morbidity and mortality in newborn infants. Recent evidence suggests nosocomially acquired viral respiratory tract infections (VRTIs) are not uncommon in the NICU. The goal of this study was to assess the association between nosocomial VRTIs, neonatal respiratory disease, and the health care related costs. METHODS: A matched case–control study was conducted in 2 tertiary NICUs during a 6-year period in Nottingham, United Kingdom. Case subjects were symptomatic neonatal patients with a confirmed real-time polymerase chain reaction diagnosis of a VRTI. Matched controls had never tested positive for a VRTI. Multivariable logistic regression was used to test for associations with key respiratory outcomes. RESULTS: There were 7995 admissions during the study period, with 92 case subjects matched to 183 control subjects. Baseline characteristics were similar, with a median gestation of 29 weeks. Rhinovirus was found in 74% of VRTIs. During VRTIs, 51% of infants needed escalation of respiratory support, and case subjects required significantly more respiratory pressure support overall (25 vs 7 days; P< .001). Case subjects spent longer in the hospital (76 vs 41 days; P< .001), twice as many required home oxygen (37%; odds ratio: 3.94 [95% confidence interval: 1.92–8.06]; P< .001), and in-hospital care costs were significantly higher (£49 664 [$71 861] vs £22 155 [$32 057]; P< .001). CONCLUSIONS: Nosocomial VRTIs in neonatal patients are associated with significant greater respiratory morbidity and health care costs. Prevention efforts must be explored.